Empowering communities through social learning: Enhancing engagement in waste management at Mandiri Kasturi - Fajri Hidayatul; Saputra Boni; Pegi Andre Lofika; Renaldi Irfan; Halawa Historis Soterman; Wahyuni Nila (E3S Web of Conferences)
A clean and healthy environment is a crucial element in the well-being of society. However, waste management in many areas, including Mandiri Kesturi, remains a significant challenge, especially amid rapid urbanization and population increase. This research explores how community-based approaches and “social learning” can improve community engagement in waste management. By involving the community in sorting to recycling, this approach improves waste management efficiency and creates sustainable environmental awareness. This case study uses a descriptive qualitative method in the Mandiri Kesturi community, with participants from community members and local leaders actively participating in the waste management program. The results showed that social learning within the community could optimize participation and create a sense of collective responsibility in maintaining environmental cleanliness. This empowerment model is expected to be applied in other communities facing similar challenges.